Effects of subthalamic deep brain stimulation on striatal metabolic connectivity in a rat hemiparkinsonian model - Nadine Apetz; Elena Kordys; Mascha Simon; Britta Mang; Markus Aswendt; Dirk Wiedermann; Bernd Neumaier; Alexander Drzezga; Lars Timmermann; Heike Endepols (Disease Models & Mechanisms, 2019)
Deep brain stimulation (DBS) in the subthalamic nucleus (STN) has been successfully used for the treatment of advanced Parkinson's disease, although the underlying mechanisms are complex and not well understood. There are conflicting results about the effects of STN-DBS on neuronal activity of the striatum, and its impact on functional striatal connectivity is entirely unknown. We therefore investigated how STN-DBS changes cerebral metabolic activity in general and striatal connectivity in particular. We used ipsilesional STN stimulation in a hemiparkinsonian rat model in combination with [18F]FDOPA-PET, [18F]FDG-PET and metabolic connectivity analysis. STN-DBS reversed ipsilesional hypometabolism and contralesional hypermetabolism in hemiparkinsonian rats by increasing metabolic activity in the ipsilesional ventrolateral striatum and by decreasing it in the contralesional hippocampus and brainstem. Other STN-DBS effects were subject to the magnitude of dopaminergic lesion severity measured with [18F]FDOPA-PET, e.g. activation of the infralimbic cortex was negatively correlated to lesion severity. Connectivity analysis revealed that, in healthy control animals, left and right striatum formed a bilateral functional unit connected by shared cortical afferents, which was less pronounced in hemiparkinsonian rats. The healthy striatum was metabolically connected to the ipsilesional substantia nigra in hemiparkinsonian rats only (OFF condition). STN-DBS (ON condition) established a new functional striatal network, in which interhemispheric striatal connectivity was strengthened, and both the dopamine-depleted and the healthy striatum were functionally connected to the healthy substantia nigra. We conclude that both unilateral dopamine depletion and STN-DBS affect the whole brain and alter complex interhemispheric networks.